Pengaruh Kepuasan Kerja dan Komitmen Organisasional Terhadap Program Pensiun Dini pada PT. Telkom Indonesia Tbk Divisi Regional V Jawa Timur - Yogi Yunanto (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2016)
This study aims to analyze the effect of job satisfaction and organizational commitment on the early retirement program of the Regional Telecommunications Division of Indonesia V East Java. The data used in this study were obtained from questionnaires, literature studies, and interviews with parties related to the research objectives. The analysis tool uses several regression hypothesis tests, namely the F test and t test. Total sample of 76 employees using the Simple Random Sampling method. The results of the study show that job satisfaction and organizational commitment simultaneously have a negative and significant effect on the early retirement program of the Regional Telecommunications Division of Indonesia V, East Java. Partially, the variable of job satisfaction has the greatest influence on the early retirement program. The value obtained from this study is R Square of 0224, which means that 22.4% of the variation in early retirement programs is explained by variations in job satisfaction and organizational commitment variables, the remaining 77.6% is explained by other variables outside this study